RESEARCH ON METHODS OF KINSHIP TERMS ANALYSIS - Ochilova Gulnora Ulashevna (Western European Studies, 2025)
The study of kinship systems, without exaggeration, has long been one of the main topics of ethnology. The system of kinship terms of different peoples has always been a source of interest for various tourists visiting a given country, and has been an object of research by ethnologists long before the fields of ethnography and ethnology took their place among the humanities.
Keywords: ethnology; kinship system; linguistic approach